Radiation induced contrast enhancement after proton beam therapy in patients with low grade glioma - how safe are protons? - Harrabi, Semi B.; Nettelbladt, Bastian von; Gudden, Clemens; Adeberg, Sebastian; Seidensaal, Katharina; Bauer, Julia; Bahn, Emanuel; Mairani, Andrea; Alber, Markus; Haberer, Thomas; Debus, Jürgen; Herfarth, Klaus (Radiotherapy and oncology, 2022)
Purpose - The optimal treatment strategy for low-grade glioma (LGG) is still a matter of controversy. Considering that the prognosis is typically favorable, the prevention of late sequelae is of particular importance. Proton beam therapy (PRT) has the potential to further reduce the burden of treatment related side effects. We set out to evaluate the clinical outcome of proton irradiation with a particular focus on morphologic features on magnetic resonance imaging (MRI). - Methods - We assessed prospectively 110 patients who received radiotherapy with protons for histologically proven LGG. Clinical and radiological information were analyzed resulting in more than 1200 available MRI examinations with a median follow-up of 39 months. Newly diagnosed contrast-enhancing lesions on MRI were delineated and correlated with parameters of the corresponding treatment plan. A voxel-based dose-matched paired analysis of the linear energy transfer (LET) inside vs outside lesions was performed. - Results - Proton beam irradiation of patients with low-grade glioma results in overall survival (OS) of 90% after seven years. Median progression free survival had not yet been reached with surviving fraction of 54% after seven years. The incidence of temporary or clinically silent radiation induced contrast enhancement was significantly higher than previously assumed, however, symptomatic radiation necrosis was only detected in one patient. These radiation-induced contrast-enhancing lesions were almost exclusively seen at the distal beam end of the proton beam. In 22 out of 23 patients, the average LET of voxels inside contrast-enhancing lesions was significantly increased, compared to dose-matched voxels outside the lesions. - Conclusion - Symptomatic radiation necrosis following PRT was as rare as conventional photon-based treatment series suggest. However, the increased incidence of asymptomatic radiation-induced brain injuries with an increased average LET observed in this cohort provides strong clinical evidence to support the hypothesis that the relative biological effectiveness of protons is variable and different to the fixed factor of 1.1 currently used worldwide.
Available online 29 December 2021, version of record 12 January 2022
Gesehen am 02.08.2022